Pengaruh teknik Cognitive restructuring Studi Literatur Kitab Ta`lim Muta’alim untuk Mengatasi Self Esteem Rendah Pada Siswa SMP Al-Jauhari Tahun Ajaran 2025/2026 - Puji Maulana; Aminatul Fadilah (Journal of Education Counseling, 2026)
Self-esteem is a crucial psychological factor in individual development and students' academic achievement. When self-esteem is low, students are at risk of experiencing various psychological issues, including lack of confidence, social anxiety, and decreased motivation to learn. The research focuses on the following problems: (1) Does the cognitive restructuring technique through literature study of Ta’lim Muta’allim effectively address diagnostic issues among students at SMP Al-Jauhari in the 2024/2025 academic year? (2) Does the cognitive restructuring technique through literature study of Ta’lim Muta’allim effectively address emotional issues among students at SMP Al-Jauhari in the 2024/2025 academic year? The aims of this study are: (1) To determine the effect of the cognitive restructuring technique through literature study of Ta’lim Muta’allim on addressing diagnostic issues among students at SMP Al-Jauhari in the 2024/2025 academic year. (2) To determine the effect of the cognitive restructuring technique through literature study of Ta’lim Muta’allim on addressing emotional issues among the same student group. This research uses a quantitative method with an experimental and correlational design. Primary data sources include the school principal, counseling teachers, and eighth-grade students. Secondary data sources consist of scientific books and academic journals. Data collection techniques include observation, questionnaires, interviews, and documentation. The sampling technique used was purposive sampling with 30 respondents. The data were analyzed using simple linear regression. The findings of this study conclude that: (1) There is no significant effect of the cognitive restructuring technique through literature study of Ta’lim Muta’allim on addressing diagnostic issues among students at SMP Al-Jauhari for the 2025/2026 academic year (H₀ accepted, Hₐ rejected). This conclusion is based on the obtained significance value of 0.120 > 0.05 and a T-value of 1.603 < 4.20. (2) There is no significant effect of the cognitive restructuring technique on addressing emotional issues among students at SMP Al-Jauhari in the 2024/2025 academic year (H₀ accepted, Hₐ rejected). This is based on an R-square coefficient value of 0.084 < 0.3601, indicating that only 8.4% of the variance is explained by the respondents' confidence level, while the remaining 91.6% is explained by other factors. The calculated regression coefficient value of 0.228 indicates that a one-unit increase in the cognitive restructuring technique corresponds to a 0.228-point increase in problem scores.